IOT BASED FLOOD DETECTING AND MONITORING SYSTEM USING RASPBERRY PI (International Journal of Food and Nutritional Sciences, 2022)
Floods are one of the most devastating natural disasters, causing significant damage to life, property, and infrastructure. In recent years, the advent of the Internet of Things (IoT) has revolutionized disaster management, enabling real-time monitoring and response. This project focuses on developing an IoT-based flood detection and monitoring system using Raspberry Pi, aiming to provide an efficient and reliable early warning system. The proposed system integrates multiple sensors to monitor critical parameters like water level, rainfall intensity, and temperature. Data from these sensors is processed by the Raspberry Pi, which then transmits the information to a cloud server for analysis and visualization. Alerts are generated and sent to relevant authorities and the public through various communication channels, including SMS, email, and mobile apps. The system's ability to provide real-time data and early warnings can significantly reduce the impact of floods by enabling timely evacuation and response efforts. The project also explores the potential of integrating machine learning algorithms for predictive analysis, enhancing the system's capability to forecast flood events based on historical data.